Estudo observacional e comparativo da estrutura e função cardíaca entre homens e mulheres residentes da região norte de Mato Grosso - Rauber, Bruno Jonas (2022)
The percentage of chronic non-communicable diseases is growing globally and is generally higher among men. The aim of the study was to compare the structure and function of the heart between male and female genders. This is a descriptive and cross-sectional study, in a sample of adult individuals by convenience (n=100), of both genders, seen in a Cardiology Clinic in the Municipality of Sinop, between August and December 2019. The project was approved by the Research Ethics Committee of UFMT (protocol no. 08745418.7.0000.8097). After the general description, the individuals were divided into two groups, being: male (n=40) and female (n=60). The echocardiographic variables of cardiac morphology and function, as well as the general characteristics, were compared between the groups (Student's t test). The confidence level was 95%. The variables body mass index and blood pressure were not statistically different between the two groups, however, there was a difference in the variables age and the height, both being lower in the female gender. Regarding the variables of cardiac structure, the female group had smaller values of LV diastolic and systolic diameters, aortic diameter, and lower thicknesses of the LV posterior wall and interventricular septum when compared to males. As for the indicators of diastolic function, there was no difference between the groups for the variables E/A and E/e'. Regarding the indicators of systolic function, the female group showed lower values of LV end-diastolic and end-systolic volumes while it showed increased ejection fraction and LV endocardial shortening. The female group presents lower values of some variables of cardiac structure and increased systolic function, which seems to be a characteristic associated with physiological differences in body composition, such as weight and height, between men and women.